2007
DOI: 10.1038/oby.2007.574
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends of Obesity and Cardiovascular Risk Factors in a Mediterranean Population

Abstract: Research Methods and Procedures: Subjects were Spanish men (n ϭ 2383) and women (n ϭ 2525) 25 to 74 years old, examined in 1994 to 1995 and 1999 to 2000 in two independent population-based cross-sectional surveys in the northeast of Spain. Lifestyle measures, CRFs, and anthropometric variables were analyzed. Results: Over the 5 years of the study, mean age-standardized BMI increased by 1.0 units in men and by 0.8 units in women. At the same time the prevalence of obesity increased from 15.4% to 21.9% in men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 25 publications
(26 reference statements)
3
18
2
Order By: Relevance
“…In addition, when analyzed the proportion of elderly with the combination of both normal categories, 63% of old men had no risk for obesity and abdominal obesity, while only 32% of the women were in this category. The proportions for obesity and abdominal obesity found in this study, and the higher quantity of women at risk compared to men, are similar to those presented for American (Freiberg et al, 2008), European (Garcia-Alvarez et al, 2007;Schroder et al, 2007), and Asian populations (Li et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, when analyzed the proportion of elderly with the combination of both normal categories, 63% of old men had no risk for obesity and abdominal obesity, while only 32% of the women were in this category. The proportions for obesity and abdominal obesity found in this study, and the higher quantity of women at risk compared to men, are similar to those presented for American (Freiberg et al, 2008), European (Garcia-Alvarez et al, 2007;Schroder et al, 2007), and Asian populations (Li et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Despite the well-known effects of hypertension on health (Lewington et al, 2002), its prevalence has increased in several countries (Ostchega et al, 2007, Schroder et al, 2007. In Brazil, the prevalence of hypertension is estimated to be 9% in children and adolescents (Moura et al, 2004), 24% in adults (Marcopito et al, 2005) and 46% in elderly (Zaitune et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…The obesity epidemic greatly affects south European countries [11,12]. A positive energy balance is the driving force of this epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Olive oil consumption without energy compensation within the total diet may increase the risk of energy overconsumption and consequently lead to weight gain. It has been suggested that a diet rich in olive oil, even in the Mediterranean context, might be responsible for the increasing obesity prevalence rates in south European countries [11,12]. However, the relevant data is limited [8,13,14].…”
Section: Introductionmentioning
confidence: 99%